How Do Industries and Firms Respond to Changes in Local Labor Supply? - Christian Dustmann; Albrecht Glitz (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2011)
In this paper, we investigate how changes in the skill mix of local labor supply are absorbed by the economy. We distinguish between three adjustment mechanisms: through factor prices, through an expansion in the size of those production units that use the more abundant skill group more intensively, and through more intensive use of the more abundant skill group within production units. We investigate which of these channels is dominant. We contribute to the existing literature by analyzing these adjustments on the level of firms, rather than industries, and by assessing the role of new firms in the absorption process of labor supply shocks. Our analysis is based on administrative data, comprising the entirety of firms in Germany over a 10 year period. We find that, while factor price adjustments are important in the non-tradable sector, labor supply shocks do not induce factor price changes in the tradable sector. In this sector, most of the adjustment to changes in relative factor supplies takes place within firms by changing relative factor intensities. Given the non-response of factor prices, this finding points towards changes in production technology Our results further show, that firms that enter and exit the market are an important additional channel of adjustment. Finally, we demonstrate that an industry level analysis is likely to over-emphasize technology-based adjustments.
Keywords: F1; J2; J61; L2; O3; 330; Immigration; Endogenous Technological Change; Firm Structure